Integrated Risk Management for Energy Efficiency: A Case Study of Batam’s Manufacturing Sector - Ayub Timba; Erkata Yandri; Omrie Ludji; Rendy Sidharta; Clizardo Amaral; Ratna Ariati (Grimsa Journal of Science Engineering and Technology, 2025)
The manufacturing sector in Batam faces increasing pressure from rising energy costs and operational inefficiencies. This study investigates how integrating risk management frameworks, specifically ISO 31000 and FMEA, can enhance energy efficiency in manufacturing operations. A mixed-methods approach was employed, combining quantitative analysis of energy consumption data from selected firms with qualitative insights from interviews with key industrial stakeholders. Baseline energy performance was established, and operational risks were assessed and prioritized. Findings show that outdated machinery, poor maintenance, and unplanned downtimes significantly contributed to energy inefficiency. Implementation of risk-based interventions led to measurable improvements in energy use and cost reduction. Firms adopting the integrated approach reported that 15% energy saving in PT X results in operational cost savings of $ 29.994, and 10% energy saving in PT Y results in operational cost savings of $ 23.952. The Return on Investment (ROI) from implementing an integrated energy risk management strategy is estimated to reach 18 months to 20 months, based on reduced energy consumption and increased productivity. The study underscores the importance of tailored risk-energy frameworks in industrial settings and suggests avenues for future research in broader contexts.